Condylomata Acuminata in Children: Report of Two Rare Cases - Yuri Widia; Shinta Dewi Rahmadhani; Sawitri Sawitri; Afif Nurul Hidayati (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2017)
Background: Condylomata acuminata are mostly found in adult patients through sexual contact. Non-sexual transmission should be considered in children with condylomata acuminata. There are no Food Drug Administration (FDA) guidelines approved for condyloma acuminata in children less than 12 years old. Purpose: To report two rare cases of condylomata acuminata in children. Cases: Two girls, aged 1 and 2 years old came at different times to Dermatology and Venereology Outpatient Clinic Dr. Soetomo General Hospital with perianal tumors. Both were born by vaginal delivery. There was no history of the same disease on the genital or the skin of both parents. Physical examinations on the perianal area were multiple flesh-colored papules with ‘cauliflower’ appearance. There was no sign or symptom of sexual abuse. Histopathological examinations in both patient show epidermis with hyperkeratosis, acanthosis, papilomatosis, some epithelial cell show koilocytosis. On the dermis layer there were proliferation from capillary blood vessel, infiltration mononuclear, intact membrane basale and no sign of malignancy. Human papillomavirus (HPV) subtypes examination results were type 11. Discussion: Trichloroacetic acid (TCA) was giving different results on both cases. The patient who did not show improvement with TCA was consulted to pediatric surgery to get electrodessication therapy by hefrycauter. Conclusion: Accurate history and physical examination isneeded to determine the mode transmissions of condylomata acuminata in children. Human papillomavirus (HPV) subtypes examination is not routinely performed and has limitation to determine the mode of transmission, especially in children. Perinatal transmission should be considered in children up to 2 years old. Multiple modalities are available for the treatment of warts in children.